The use of cognitive and metacognitive strategies in collaborative strategic reading for comprehension: an investigation among first-year students in FELTE, ULIS = Chiến thuật nhận thức và siêu nhận thức trong hoạt động hợp tác đọc hiểu: một nghiên cứu về sinh viên năm nhất khoa sư phạm tiếng Anh, Trường Đại học Ngoại ngữ - Đại học quốc gia Hà Nội - Nguyễn, Thanh Hoa (2020)
Cognitive and metacognitive strategies are often claimed to have significant influence on learner’s language learning process, especially reading comprehension. The effect is also the same with collaborative strategic reading. Recognizing the stunning effect of these strategies on reading comprehension, the author would like to investigate the current use of cognitive and metacognitive strategies in collaborative strategic reading for comprehension. This research mainly figures out the frequency in the use of cognitive and metacognitive strategies in collaborative strategic reading and the effect(s) of those strategies on comprehension. First-year students in FELTE, ULIS are chosen to take part in this research. After completing a questionnaire about their language learning strategies, six students are selected for observation. One student which has high tendency in using cognitive strategies partners with one with high frequency in using metacognitive strategies. Together, they accomplish a reading task with seven reading comprehension questions. The result reveals that (1) cognitive strategies tend to be used more often than the metacognitive strategies and the most widely-used strategies is highlighting; and (2) student’s comprehension of the reading task is good and there is a change in their strategy use during the reading collaboration.